Pedagogical technology of M.Shchetinin in the context of new challenges of modern pedagogy - Davidova, Rufina (MMIT Proceedings, 2024)
In this article, the author provides information about the pedagogical technology of M. P.Shchetinin, which reveals the creative abilities and skills of students, promotes the development of communication and social skills. The basic principles and goals of this technology are described, which contribute to the in-depth mastery of educational material.